2020
DOI: 10.3390/nano10010110
|View full text |Cite
|
Sign up to set email alerts
|

ToxTracker Reporter Cell Lines as a Tool for Mechanism-Based (Geno)Toxicity Screening of Nanoparticles—Metals, Oxides and Quantum Dots

Abstract: The increased use of nanoparticles (NPs) requires efficient testing of their potential toxic effects. A promising approach is to use reporter cell lines to quickly assess the activation of cellular stress response pathways. This study aimed to use the ToxTracker reporter cell lines to investigate (geno)toxicity of various metal- or metal oxide NPs and draw general conclusions on NP-induced effects, in combination with our previous findings. The NPs tested in this study (n = 18) also included quantum dots (QDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Environmental exposure to MnO NPs can occur as a result of occupational exposure in manganese ore processing, the metallurgy industry, metalworking, welding, and various potential biomedical applications [20][21][22]39 . MnO NP have been shown to cause impairment of dopaminergic neurons and induce inflammation in the brain, increase in oxidative stress and apoptosis in alveolar epithelial cells, and increase oxidative stress and DNA damage in mouse embryonic stem cells, human breast cancer epithelial cells, and human fibrosarcoma epithelial cells [39][40][41][42] . However, few studies have evaluated at the effects of MnO NP toxicity on intestinal epithelial cells, even though the primary route of exposure would be oral or ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental exposure to MnO NPs can occur as a result of occupational exposure in manganese ore processing, the metallurgy industry, metalworking, welding, and various potential biomedical applications [20][21][22]39 . MnO NP have been shown to cause impairment of dopaminergic neurons and induce inflammation in the brain, increase in oxidative stress and apoptosis in alveolar epithelial cells, and increase oxidative stress and DNA damage in mouse embryonic stem cells, human breast cancer epithelial cells, and human fibrosarcoma epithelial cells [39][40][41][42] . However, few studies have evaluated at the effects of MnO NP toxicity on intestinal epithelial cells, even though the primary route of exposure would be oral or ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…This issue contains mostly data from in vitro studies. In addition to classical cell lines such as hamster and human fibroblasts [ 1 , 2 ] or human lung cells [ 3 , 4 ], new models have been also used for investigating nanomaterials genotoxicity: ToxTracker reporter cell lines [ 5 ], human amniotic cells [ 6 ] and 3D HepG2 spheroids [ 7 ]. In this issue, three papers also deal with in vivo studies: on the plant Allium cepa [ 8 ], on the tadpoles of Xenopus laevis [ 9 ] and on rats [ 10 ].…”
mentioning
confidence: 99%
“…Concerning the role of the physico-chemical characteristics, it was reported that the surface area is one of the dose metrics showing a better correlation with the genotoxicity of quantum dots [ 5 ], while the metal/coating agent ratio is a key parameter for the toxicity observed with the commercially available AgNPs formulation Argovit™ [ 8 ]. Similarly, the thermal reduction of graphene oxides generates a material that was no longer genotoxic at low concentrations [ 9 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations